Edged-based smoothed point interpolation method for acoustic radiation with perfectly matched layer. (15th September 2020) - You, Xiangyu; Chai, Yingbin; Li, Wei
Abstract: It is known that for exterior acoustics the domain-based finite element method always encounters the accuracy loss for high wavenumbers and the difficulty in dealing with the Sommerfeld radiation condition. In this work, by using the polynomial and radial bases with specific node-selection schemes, the point interpolation method with the generalized gradient smoothing technique is employed to improve the accuracy for acoustic computations. The appropriately softened acoustical stiffness of the discrete model is constructed based on the edge-based smoothing domains via the gradient smoothing technique. In addition, the perfectly matched layer technique enables the smoothed point interpolation method to investigate exterior acoustics. The complex coordinate transformation is utilized to determine the proper parameters for the perfectly matched layer through theoretical and numerical analyses. Several typical acoustic problems are analyzed, revealing that better accuracy is obtained by the present method compared with the finite element method, especially for high wavenumbers. Highlights: ES-PIM/RPIM is first extended to analyze acoustic radiation problems with the PML technique. The PML technique based on the smoothing domains for various SPIM/RPIM is effective for exterior acoustics. ES-PIM/RPIM provides more accurate solutions than the conventional FEM for acoustic radiation problems in high wavenumbers.